The Impact of Telework Work-Family Conflict and Work Overload on Work Stress During the Covid-19 Pandemic 2020-2022 (Systematic Literature Review and Bibliometric Analysis) - Arumdani, Kurnia; Soetjipto, Budi Eko; Sopiah, Sopiah (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2024)
This study investigates the outcomes of work-related stress resulting from a blend of WFC and increased workload amid the COVID-19 pandemic, particularly in teleworking. The study employed a SLR as a means of data exploration, incorporating literature bibliometrics for data processing and subsequently subjecting the data to analysis through the VOSviewer program. The investigator examined citations from the Scopus database, evaluating 334 articles, among which 62 were published from 2020 to 2022. The VOSviewer program was leveraged to evaluate co-authorship, co-accuracy, and citations, promoting a more nuanced understanding of the results. This review furnishes a focused bibliographic viewpoint for prospective researchers, assisting them in navigating the evolving dynamics of work-family conflicts, particularly accentuated among individuals managing multiple roles or shouldering caregiving responsibilities during the pandemic. The study underscores the merits and challenges of teleworking, highlighting the intricacies of establishing boundaries between work and caregiving roles. Neglecting these boundaries may precipitate job stress for remote workers. In essence, this research illuminates the characteristics of pertinent articles and the ramifications of teleworking, WFC and Excessive workload on work stress during the pandemic. It advocates for further investigation to deepen comprehension of the intricate interplay between these factors.